Job satisfaction and moral distress of nurses working as physician assistants: focusing on moderating role of moral distress in effects of professional identity and work environment on job satisfaction - Minsub Kim; Younjae Oh; Joo Yun Lee; Eunhee Lee (BMC, 2023)
Abstract Background Physician assistant was created in response to a shortage of physicians. However, this profession is not officially recognized in Korea. Many nurses are working as physician assistants. Their job satisfaction was low due to role conflict. Job satisfaction plays a major role in providing high quality nursing. This study aimed to investigate effects of work environment and professional identity on job satisfaction and identify the mediating role of moral distress in such effects. Methods Participants were 112 nurses working as physician assistants. They were recruited from three General Hospitals. A questionnaire scale was used to collect data. Data were analyzed using frequency, descriptive statistics, independent t-test, one-way ANOVA, Pearson correlation, and Macro Model 4 with SPSS Statistics. Results Job satisfaction of nurses working as physician assistants had a score of 3.08 out of 5. It showed significant associations with work environment and professional identity. Moral distress had a partial mediating role in relationships of job satisfaction with work environment and professional identity. Conclusion Many nurses are working as physician assistants, although physician assistant as a profession is not officially recognized in Korea. Nurses working as physician assistants experience confusion about their professional identity and moral distress. For better nursing outcomes, physician assistant policy should be improved, and various strategies should be provided to improve their job satisfaction.